Women`s artistic gymnastics in Australia and New Zealand: A foucauldian examination of the relationship between sport governance and consumption - Kerr, R.; Barker-Ruchti, N. (Journal of Sport and Social Issues, 2015)
This article relates the Australian and New Zealand women`s artistic gymnastics governance systems to the micro-level conduct of coaches, gymnasts, and parents. Two ethnographic studies conducted in these countries examined how gymnasts, parents, and coaches reacted to and produced training realities. We employ a Foucauldian perspective of consumption to analyze the data. The results demonstrate different types of consumer mentalities. In Australia, where governance is driven by pressure to return investment, coaches, gymnasts, and parents disciplined their selves and consumption to fulfill prescribed expectations. In New Zealand, where gymnastics does not receive financial support and thus the National Sporting Organisation cannot prescribe particular performance results, gymnasts and parents negotiated their consumption.